Pendampingan Pembelajaran Anak Sekolah melalui Pendirian Sanggar Belajar di Desa Srikaton - Imam Azro’i; Arif Chasannudin; Nur Khofifah; Suparti S (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
This community development is conducted based on the problem of children’s difficulties in learningoutside formal schools. This difficulty is due to the lack of human resources in guiding children and theabsence of tutoring institutions. The community in Srikaton Village hopes that there will be a place oflearning other than formal school that can be a recreational place for children in learning that providesbooks and tutoring activities. Empowerment carried out in Srikaton Village is by establishing a SanggarBelajar which has tutoring activities, English courses, coloring, collage art, and reading. Thesustainability of this program resulted in a Sanggar Belajar managed by the Karang Taruna of SrikatonVillage.